Impact of Auditor Report Changes on Financial Reporting Quality and Audit Costs: Evidence from the United Kingdom - Reid, Lauren C.; Carcello, Joseph V.; Li, Chan; Neal, Terry L.; Francis, Jere R. (Contemporary Accounting Research, 2019)
ABSTRACT While substantial revisions to auditor reporting requirements are being implemented internationally, the impact of these reforms on financial reporting quality is unknown. We exploit the United Kingdom's recent auditor reporting changes and find that the United Kingdom's new reporting regime is associated with an improvement in financial reporting quality as proxied by significant decreases in absolute abnormal accruals and the propensity to just meet or beat analyst forecasts, and a significant increase in earnings response coefficients. As for audit costs, we do not find a significant change in audit fees or audit delay surrounding the implementation of the new reporting regime. Taken together, the results of this study suggest that new auditor reporting requirements are associated with a significant improvement in financial reporting quality without detecting a significant increase in audit costs.